Principles of Social Justice in Land Law in Indonesia - Parameswari, Andini; Choirina A, Ana; Ayu N, Anisa; Angely, Angely; Chillava A, Achilla; KN, An Nuur; Rachma H, Alfina (Jurnal Legisci, 2023)
This study aims to examine the principles of social justice underlying land law in Indonesia. Equitable distribution and fair access to land resources can only be guaranteed through establishing and applying land law principles based on social justice. The study identifies social justice principles embedded in Indonesia's land law framework, including land ownership, utilization, and administration principles. This study uses comparative law approaches and normative analysis to assess how social justice principles are reflected in land-related laws, regulations, and policies. Furthermore, this study recognizes the challenges and obstacles to applying social justice principles in land law practice. The findings of this study aim to provide an in-depth understanding of the relationship between social justice principles and land law in Indonesia, as well as provide recommendations to improve the alignment of social justice principles with land law practice in the future.